2011
DOI: 10.1007/s12072-011-9266-y
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C: a predictor of hepatorenal syndrome in patients with liver cirrhosis

Abstract: Serum CysC level may be considered a predictor of HRS and mortality in patients with liver cirrhosis and ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
2
28
0
3
Order By: Relevance
“…For this reason, dilution hyponatremia and low sodium output in the urine are expected to be very common in patients with HRS. This association has been confirmed by published data [4][5][6] . It is however necessary to rule out, pseudohyponatremia in acute on chronic liver failure 21 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…For this reason, dilution hyponatremia and low sodium output in the urine are expected to be very common in patients with HRS. This association has been confirmed by published data [4][5][6] . It is however necessary to rule out, pseudohyponatremia in acute on chronic liver failure 21 .…”
Section: Discussionsupporting
confidence: 84%
“…Two studies found serum sodium was not a significant, independent HRS predictor 5,8 and two did 3,9 . The fifth paper was only a case-control design 10 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have suggested that serum cystatin C is a more sensitive marker of GFR than SCr since it freely crosses the glomerular membrane to be reabsorbed and metabolized in the proximal tubular cells, without being eliminated [7]. Cystatin C has been also shown to be a predictor of HRS and mortality in patients with liver cirrhosis and ascites [9].…”
Section: Discussionmentioning
confidence: 99%
“…Other tubular proteins unregulated by injury include Neutrophil Gelatinase-Associated Lipocalin (NGAL), Kidney injury molecule 1 (KIM-1), and Liver-type fatty acid binding protein (L-FABP) [7][8][9][10]. In animal models, NGAL is released in the urine following an ischemic or nephrotoxic insult.…”
Section: Discussionmentioning
confidence: 99%